2019
DOI: 10.1007/s40279-019-01189-4
|View full text |Cite
|
Sign up to set email alerts
|

Change of Direction Assessment Following Anterior Cruciate Ligament Reconstruction: A Review of Current Practice and Considerations to Enhance Practical Application

Abstract: Change of direction (CoD) has been indicated as a key mechanism in the occurrence of anterior cruciate ligament (ACL) injury during invasion sports. Despite these associations, assessments of knee function in athletic populations at the time of return to sport following ACL reconstruction (ACLr) have often focused on strength and single-leg hop tests, with a paucity of evidence to describe the CoD characteristics. Therefore, the aim of this narrative review was to describe the movement strategies exhibited fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 81 publications
0
24
0
2
Order By: Relevance
“…These findings, accordingly, have important implications for coaches and sport science professionals tasked with preparing team sport athletes for competition demands. Given the significance of maximal horizontal deceleration ability to team sport performance [ 2 ], injury risk [ 6 ] and the effectiveness of return-to-play protocols [ 56 ], future research should (a) investigate the NMP determinants of horizontal deceleration ability across different sports and performance levels, and (b) seek to determine the efficacy of training interventions specifically focused on improving maximal horizontal deceleration ability.…”
Section: Discussionmentioning
confidence: 99%
“…These findings, accordingly, have important implications for coaches and sport science professionals tasked with preparing team sport athletes for competition demands. Given the significance of maximal horizontal deceleration ability to team sport performance [ 2 ], injury risk [ 6 ] and the effectiveness of return-to-play protocols [ 56 ], future research should (a) investigate the NMP determinants of horizontal deceleration ability across different sports and performance levels, and (b) seek to determine the efficacy of training interventions specifically focused on improving maximal horizontal deceleration ability.…”
Section: Discussionmentioning
confidence: 99%
“…Movement happens with some degree of cognitive processing in order for the proper response to occur. Research has demonstrated those with a history of concussion or anterior cruciate ligament reconstruction have slowed dual-task performance (Marques et al, 2020 ; Ness et al, 2020 ). This slowing of dual-task neural processing may lead to differences in performance capabilities which may also lead to an elevated risk for musculoskeletal injury (Wilkerson et al, 2017 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Motion capture systems are recognized as the gold standard for movement analysis and are used to measure joint moments, ground reaction forces, contact times, velocities, joint angles and speed of COD movement. [19][20][21][22][23] However, motion capture systems are not easily transported to field settings. 19,24,25 Global positioning systems (GPS) are a potential feasible on-field monitoring system, but there are limitations with GPS in recognizing highspeed direction changes.…”
Section: Introductionmentioning
confidence: 99%
“…There are previous reviews presenting the challenges on the use of IMUs for measuring ground reaction forces 40 and the use of regression techniques for continuous biomechanical monitoring. 41 In addition, the review by Marques et al 23 underlines the need for viable solutions for onpitch/court measurements to 'bridge the gap' between laboratory based measures and real-life situations.…”
Section: Introductionmentioning
confidence: 99%